“FACTORY OF PROCESSES” – A NEW FORMAT OF EDUCATIONAL PROCESS ORGANIZATION AT HIGHER EDUCATION INSTITUTION - A. A. Kurmangulov; J. S. Reshetnikova; R. N. Bagirov; O. I. Frolova; N. S. Brynza (Высшее образование в России, 2018)
The article highlights the technology of organization of educational process in higher educational institution with the application of the interactive method of training – “factory of processes”. The article adduces the comparative characteristics of the “factory of processes” methodology, the general content-technological determinants with the format of business game, as well as their distinctive features. The authors note the sufficiently large scenary variability potential of the “factory of processes” method with the obligatory inclusion of a number of stages. The experience of implementing the “factory of processes” in the educational process of the Tyumen State Medical University in the framework of the program “Lean production in health care” is described. The article shows the high potential for incorporating the format of the “factory of processes” technology into the educational process with obtaining the necessary competencies and aiming at using the acquired skills in further practical activities.